Chemistry Teaching in Tefé city (AM) during the Covid-19 Pandemic (Research, Society and Development, 2022)
The pandemic caused by Coronavirus has had impacts in several areas of society and would be no different in education. This paper aims describe chemistry teaching during the COVID-19 pandemic in Tefe city, Amazon countryside by to understand what the challenges were faced by chemistry teachers during the pandemic period. This is qualitative research of the descriptive - exploratory approach. As a result, it was verified that teachers had difficulties in teaching their classes remotely due to the lack of internet and/or an internet that oscillated and had low speed. It was evident that in some cases the students did not have smartphones or internet access and the solution was to make the printed material available at school. Therefore, lack of investment in the qualification of teachers for the use of technologies in teaching, and the lack of quality equipment and internet were the greatest obstacles encountered by teachers and students in remote chemistry classes during the pandemic period and the positive point was related to the autonomy developed by the students.